1996
DOI: 10.1557/proc-465-1309
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Uranium Minerals on the Surface of Chernobyl “Lava”

Abstract: The formation of uranium minerals is still continuing in Chernobyl Unit No. 4. Yellow products of alteration that stain the surface of Chernobyl “lava” have been examined by SEM and X-ray diffraction methods. Secondary minerals of uranium identified are: UO4·4H2O studtite; UO3·2H2O epiianthinite; UO2·CO3 rutherfordine; also, Na4(UO2)(CO3)3 was identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 3 publications
0
60
1
2
Order By: Relevance
“…Metastudtite formed on the surface of UO 2 under irradiation with a 4 He 2+ (alphaparticle) beam, and incorporated peroxide formed by alpha-radiolysis of water [64]. Studtite has also been found on nuclear material (''lava") following the Chernobyl Nuclear Plant accident [65].…”
Section: Uranyl Peroxidesmentioning
confidence: 99%
“…Metastudtite formed on the surface of UO 2 under irradiation with a 4 He 2+ (alphaparticle) beam, and incorporated peroxide formed by alpha-radiolysis of water [64]. Studtite has also been found on nuclear material (''lava") following the Chernobyl Nuclear Plant accident [65].…”
Section: Uranyl Peroxidesmentioning
confidence: 99%
“…Given the long history of nuclear operations and related waste disposal at the AEC/DOE complex, čejkaite or its trigonal polymorph may have been physically identified and 3.37 documented in old classified or unclassified reports. More recently, čejkaite has been identified as a secondary mineral at a uranium ore deposit in the Czech Republic (Ondruš et al 2003), and possibly as an alteration product of the silicate lava that solidified from the destruction of the Chernobyl reactor core (Burakov et al 1997). …”
Section: Comparison Of Leached and Unleached C-203 And C-204 Sludge Smentioning
confidence: 99%
“…[16] Behaviour of uranium in solid solution, especially the stability of Na 4 [UO 2 (CO 3 ) 3 ], was presented by Rafalskii. [17] Burakov et al [18] reported on a number of minerals including Na 4 [UO 2 (CO 3 ) 3 ], studtite (UO 4 · 4H 2 O), epiianthinite (UO 3 · 2H 2 O), rutherfordine (UO 2 CO 3 , Na 3 H(CO 3 ) 2 · 2H 2 O) and Na 2 CO 3 ·H 2 O as yellow products of alteration that stain the surface of Chernobyl 'lava'. Catalano and Brown [19] analysed syntheticčejkaite by EX-AFS spectroscopy.…”
Section: Introductionmentioning
confidence: 99%